Conditions for Vacuum Instability in Holographic Theories with Dilaton Field - Sara Tahery; Sreeraj Nair; Pengming Zhang (Advances in High Energy Physics)
We investigate the vacuum instability in the presence of dilaton field in a holographic setup. Although the dilaton is a bulk field, it leads to the vacuum instability on the boundary. We show that the whole process crucially depends on the probe brane position and as well on the radial coordinate so that the effects of dilaton scale parameter in different regions of the bulk or for different probe brane positions are different. We also observe that in our study, the temperature can strengthen the effect of scale parameter in reducing the potential barrier. Finally, we show that this Schwinger-like effect, although is interesting by itself, does not produce a considerable pair production rate.